The Effectiveness and Feasibility of Palliative Care via Video Telemedicine for Patients with Advanced Cancer: A Nonrandomized Prospective Clinical Trial Comparing Combination of Telemedicine and in-Person Care with in-Person Care Alone - Akihiko Chida; Yasuo Hamamoto; Kenro Hirata; Yasunori Sato; Eiichiro So; Shotaro Kishimoto; Satoko Noguchi; Sara Horie; Yuki Saito; Keitaro Shimozaki; Kai Tsugaru; Kazuhiro Togasaki; et al. (Palliative Medicine Reports)
Background: Palliative care has been shown to be effective for patients with advanced cancer; however, the best approach to deliver palliative care needs to be considered. We hypothesized that a combination of palliative care via video telemedicine (TMD) and usual outpatient treatment would improve patients’ quality of life (QOL) and ameliorate depression and prognosis. Methods: Patients with advanced cancer who terminated treatment with chemotherapy were enrolled. Patients who could perform videoconferencing were assigned to the TMD group and those who could not perform were assigned to the (no TMD; control) group. The primary endpoint was QOL, which was evaluated using the difference in the Functional Assessment of Cancer Therapy-General (FACT-G) scores between baseline and one-month follow-up. Secondary endpoints included depression, measured using the Center for Epidemiological Studies Depression (CES-D) scale, overall survival, and patient satisfaction. Results: Fifty patients were included in this study (25 in each group). A comparison of measures of QOL at one month showed that the TMD group maintained a better QOL. FACT-G decreased by 0.21 and 5.96 points in the TMD and no TMD groups, respectively (p = 0.047). The TMD group maintained better QOL. There were trends suggesting improvements in depression and survival which did not reach significance. CES-D increased by 0.92 and 3.50 points in the TMD and no TMD groups, respectively (p = 0.26). Median survival time was 7.82 (3.30–14.59) and 6.37 (2.33–11.04) months in the TMD and no TMD groups, respectively. The results of the Patient Satisfaction Questionnaire suggest that video TMD could be a feasible tool in palliative care. Conclusion: Video TMD is effective in maintaining the QOL of patients with advanced cancer and is feasible based on patient satisfaction. It is desirable to further evaluate the usefulness of palliative care using video TMD and evaluate its clinical applications.